Transtheoretical Model of Behavioural Change for Oral Habit, Tobacco and Alcohol Cessation. - Anurag Satpathy (Indian Journal of Forensic Medicine & Toxicology, 2020)
The transtheoretical model of change is one of the most accepted strategies to bring about an intentionalchange. It addresses the process of change in a structured manner which can be beneficially implemented tobring about positive changes to achieve habit breaking, tobacco and alcohol cessation. In addition, it mayhelp acquire and establish positive habits such as maintenance of oral hygiene.